The local efficacy and influencing factors of ultrasound-guided percutaneous microwave ablation in colorectal liver metastases: a review of a 4-year experience at a single center. (1st January 2019) - Qin, Si; Liu, Guang-Jian; Huang, Meijin; Huang, Jun; Luo, Yanxin; Wen, Yanling; Wang, Yimin; Chen, Limei
Abstract: Purpose: To investigate the clinical effectiveness and safety of ultrasound (US)-guided percutaneous microwave ablation (MWA) for colorectal liver metastasis (CRLM) and evaluate the influencing factors of local efficacy. Methods: From January 2013 to January 2017, 137 CRLM patients accepting US-guided percutaneous MWA were included. The 2450-MHz microwave ablation system and a cooled-shaft antenna were used. All patients were regularly followed up for at least 6 months. Technical success, complete ablation, local tumor progression (LTP), complications and side effects were assessed. Logistic regression analysis was used to identify the independent prognostic factors for LTP. Results: In total, 411 lesions (mean diameter 15.4 ± 7.2 mm, range 5–67 mm) were treated. Complete ablation was achieved in 99.27% (408/411) of lesions and 97.81% (134/137) of patients. LTP occurred in 5.35% (22/411) of lesions and 16.06% (22/137) of patients. LTP was more likely to occur in lesions larger than 3 cm in diameter (OR: 14.71; p  < .001; 95% CI: 3.7 3–57.92), near a large vascular structure (OR: 7.04; p  < .001; 95% CI: 2.41–20.60), near the diaphragm (OR: 4.02; p  = .049; 95% CI: 1.05–16.11) and in patients with no response to chemotherapy before MWA (OR: 3.25; p  = .032; 95% CI: 1.14–15.30). MWA was well tolerated, with a major complication rate of 3.65%, a minor complication rate of 8.03% and a mortality rate of 0%. Fever and pain were the most common side effects after MWA. Conclusions: US-guided percutaneous MWA of CRLM is a safe and effective method that is expected to become a routine treatment for local tumor control of CRLM.